Hatchet - Paulsen, Gary (Paulsen, Gary. Brian's saga, 2007)
After a plane crash, thirteen-year-old Brian spends fifty-four days in the Canadian wilderness, learning to survive with only the aid of a hatchet given him by his mother, and learning also to survive his parents' divorce. Includes an introduction and sidebar commentary by the author.